Stardust - Gaiman, Neil (New York, NY HarperTeen, 2009)
The story of young Tristran Thorn and his adventures in the land of Faerie. He has fallen in love with beautiful Victoria Forester and in order to win her hand, he must retrieve a fallen star and deliver it to her.
Includes preview of The graveyard book (23 p. at end).
Keywords: Young men; Alex award; Movie novels; Love stories; Manners and customs; England -- Social life and customs -- 19th century; England; London (England); England -- London; Fantasy fiction; Fiction; Juvenile works